Pengaruh Model Pembelajaran Example Non Example Terhadap Motivasi Belajar Siswa Pada Materi Keberagaman dalam Bingkai Bhinneka Tunggal Ika Kelas VII SMP Sabilush Sholihin Socah - Achadiyah, Imarul; Ernawati; Indriani, Dian Eka (Penerbit STKIP PGRI Bangkalan, 2021)
This research is a quantitative study using data collection techniques, namely questionnaires and documentation. This research was conducted in class VII SMP Sabilush Sholihin Socah, the results of this study were to determine the effect of the example non-example learning model on student learning motivation on diversity material in the framework of Bhinneka Tunggal Ika class VII SMP Sabilush Sholihin Socah. The results showed that the value of r-count was 3164,115 and the r-table value is 0.361 at a significant level of 5%, which means that the r-count value is greater than the r-table value. In other words, Ha is accepted and Ho is rejected. So it can be concluded that there is an effect of the example non-example learning model on student learning motivation on diversity material in the framework of Bhinneka Tunggal Ika class VII Junior High School Sabilush Sholihin Socah.